Root and shoot studies of summer cowpea (Vigna unguiculata) and baby corn (Zea mays) under intercropping system with different levels of fertility and stress-mitigating chemicals - BIJARNIA, ANJU; TETARWAL, J P; BIJARNIA, ARJUN LAL (The Indian Journal of Agricultural Sciences, 2024)
An experiment was conducted during summer seasons of 2019 and 2020 at College of Agriculture (Agriculture University, Kota), Ummedganj, Rajasthan, to study the root and shoot of summer cowpea [Vigna unguiculata (L.) Walp.] and baby corn (Zea mays L.) under intercropping system with different levels of fertility and stress-mitigating chemicals. The experiment was laid out in a split-split plot design with 4 replications having 30 treatment combinations with 5 intercropping systems [sole cowpea; sole baby corn; cowpea + baby corn (2:1); cowpea + baby corn (3:1); and cowpea + baby corn (4:1)] in the main plot and 3 fertility levels, viz. 100; 125; and 150% RDF (Recommended dose of fertilizer) in subplot and 2 stress mitigating chemicals (0.5% CaCl2 and 1% KNO3 at flowering and pod development stage of cowpea) in sub-sub plot. Results revealed significant increase in shoot weight, root weight, root-to-shoot ratio, cowpea equivalent yield (CEY) and number and dry weight of nodules in 2:1 row cowpea + baby corn intercropping system over other row ratios. The 2:1 row ratio significantly increased root:shoot ratio of cowpea by 20.9, 15.2, and 7.3% over sole cowpea, 4:1 and 3:1 row ratio, respectively, and resulted in the highest root-to-shoot ratio for baby corn, recording 18.3, 14.5, and 6.8% increase over sole baby corn, 4:1, and 3:1 row ratios of cowpea and baby corn, respectively. Further shoot weight, root weight, root:shoot ratio in cowpea and baby corn, CEY and the number and dry weight of nodules in cowpea exhibited a notable increase in 150% RDF as compared to lower fertility levels (100 and 125% RDF). Applying 150% RDF resulted in a significantly higher root:shoot ratio for both cowpea and baby corn, with increases of 11.3 and 4.5% over 100 and 125% RDF for cowpea, and 11.6 and 5.5% over 100 and 125% RDF for baby corn, respectively. Foliar application of 0.5% CaCl2 at the flowering and pod-developing stages significantly augmented all the aforementioned parameters for both cowpea and baby corn.